ANALISIS HERMENEUTIKA PEREMPUAN DALAM LAGU RAYUAN PEREMPUAN GILA - Muhammad Farhan; Syafruddin Pohan; Noniya Dewinta; Andre Genesa Harahap (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
The unique and 'wild' lyrical rhetoric loaded and used by Nadin Amizah in the song Rayuan Perempuan Gila seems to create a chain effect that creates a new trend among its listeners. The trend that emerged, where the majority of listeners consciously opened themselves by conveying their shortcomings or declaring themselves as 'crazy women' to their partners or even to the public. Therefore, an analysis of the meaning of the song lyrics was conducted to solve the question